TRADISI NYAKAN DIWANG (Studi Analisis Pembangunan Karakter Generasi Muda Hindu di Desa Banyuatis) - Made Awanita (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2020)
The objectives of this study are: (1) to know the meaning and religious values contained in the Nyakan diwang tradition in Banyuatis Village, Banjar, Buleleng; (2) to provide an analyst with the implementation of the Nyakan diwang tradition carried out in the area in relation to the process of educating the character of the younger generation of Hindus in the Banytuatis Village, Banjar, Buleleng.This research is classified as qualitative research. The data collection technique in this study uses purposive sampling and snowball sampling. The object of the research is the Nyakan diwang tradition by the people of the Bayuatis Village, Banjar, Buleleng. Based on the object of the study, the subjects in this study were the community, the village head (Perbekel) and also the traditional prajuru of the Bayuatis Village, Banjar, Buleleng. Data collection methods used are interviews, informant determination, observation, data processing, and documentation studies.Keywords: Nyakan diwang 's Tradition History Background, Diwang's Practical Tradition, Diwang's effort to preserve and preserve; Construction of Hindu Young Generation Characters.